1990
DOI: 10.1093/carcin/11.8.1293
|View full text |Cite
|
Sign up to set email alerts
|

Human cytochrome P450IIA3: cDNA sequence role of the enzyme in the metabolic of promutagens comparison to nitrosamine activation by human cytochrome P450IIE1

Abstract: We report that, in a human cell line, human cytochrome P450IIA3 is capable of metabolizing aflatoxin B1, benzo[a]-pyrene, N-nitrosodimethylamine (NDMA) and N-nitrosodiethylamine (NDEA) to cytotoxic and mutagenic species. Cytochrome P450IIA3-mediated activation of NDMA and NDEA was compared with human cytochrome P450IIE1-mediated activation in the same cell system. P450IIE1 was more effective at activating NDMA than P450IIA3, while P450IIA3 was more effective at activating NDEA than P450IIE1. Whole cells and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(48 citation statements)
references
References 0 publications
2
46
0
Order By: Relevance
“…[19][20][21] There was no reported enzyme kinetics of CYP2A6 for AFB 1 metabolism, and the activation of AFB 1 by CYP2A6 was mainly demonstrated by mutagenesis assay. 34 Results from our metabolism and cytotoxicity studies clearly show that CYP2A13 is much more active than CYP2A6 in the metabolic activation of AFB 1 . Further studies to compare the enzyme kinetics of these human CYP enzymes in AFB 1 metabolism are warranted.…”
Section: Discussionmentioning
confidence: 80%
“…[19][20][21] There was no reported enzyme kinetics of CYP2A6 for AFB 1 metabolism, and the activation of AFB 1 by CYP2A6 was mainly demonstrated by mutagenesis assay. 34 Results from our metabolism and cytotoxicity studies clearly show that CYP2A13 is much more active than CYP2A6 in the metabolic activation of AFB 1 . Further studies to compare the enzyme kinetics of these human CYP enzymes in AFB 1 metabolism are warranted.…”
Section: Discussionmentioning
confidence: 80%
“…Studies done in the past few years have shown the involvement of several CYP enzymes in the activation of AFB1 to a mutagenic and/or cytotoxic product(s). The major contribution was assigned to CYP1A2 (35)(36)(37), CYP3A4 (38,39,(40)(41)(42), CYP2A3 (35,43,44) and the activating potency was suggested to decrease in this order (45). Apart from these enzymes, minor contributions of CYP2B1 and CYP3A3 enzymes to AFB1 activation were also shown (35,46).…”
Section: Discussionmentioning
confidence: 97%
“…Genotoxicity assays involved measurement of the umu (SOS) response in Salmonella typhimurium TA1535 harboring the plasmid pSK1001 using general procedures described elsewhere (32 (9,31,(34)(35)(36)(37) (Table 2). P450 1A2 and some other human P450s can also contribute, but they play a lesser role, even at relatively low AFB, concentrations (31,35,36,38,39). P450 3A4 forms only the genotoxic AFBI-8,9-exo-epoxide; P450 1A2 forms both the exo and the nongenotoxic endo isomers (Figure 1)(31).…”
Section: Introductionmentioning
confidence: 99%